A regionalidade presente em lexias simples, complexas e textuais na obra A Rainha do Ignoto de Emília Freitas - Vasconcelos, Márcia Maria Fonteles (2022)
Language is a constant manifestation of dynamism and representation of peoples. As instruments of social representation, linguistic phenomena allow contact with culture, customs, political and historical characterizations that are reproduced through writing and orality. When looking at literature as a possible vehicle of linguistic representation, one can verify the particularities inserted there regarding language and how this way of study operates concomitantly with social representation. It is, therefore, within this setting, that the regionalist pertinence of Emília Freitas writing adds to the linguistic discussions while denoting possibilities of unfolding, in view of the gaps identified on the subject. In this sense, the general objective of this research is to analyze the regional lexias present in the work A Rainha do Ignoto by Emília Freitas, highlighting the semantic aspects of the popular language of Ceará and the representation of those in preponderant lexical fields. For this purpose, theoretical foundations in the area of lexicology and lexicography will be used (COSERIU, 1979, 1981; MATORÉ, 1953; VILLALVA E SILVESTRE, 2014); of the lexical units that will be treated in this process (VILELA, 1979; BIDERMAN, 1978, POTTIER, 1978, BORBA, 2003); of the areas that are linked to the discussions and analyzes that will be proposed, such as the dialectological and semantic setting (DUBOIS, 1978; NASCENTES, 1953; ARAGÃO, 2020; ILLARI E GERALDI, 2004; ULLMANN, 1964) and the theories that support the studies on the lexical fields, from which one was selected that structures the final product of this research (COSERIU, 1981, 1982; WEISGERBER, 1963; VILELA, 1979). Regarding the methodological course of this proposition, the quantitative-qualitative approach is highlighted, in which, a priori, research, studies and data collection were carried out for later scrutiny that underlies the quantitative bias. The simple, complex and textual lexicons were extracted from the work A Rainha do Ignoto (2019), as outlined in the methodological processes. As far as the analysis itself is concerned, there is a greater occurrence of simple lexicons to the detriment of others, with a record of dictionary meaning in most of them, which helps to prove their regional relevance. In addition, the results show lexical fields that are equivalent to the regional cultural representations, in which the work is inserted, corroborating hypotheses and expanding the paths of study, as well as raising other reflections for further studies with non-canonical works, but which are not inferior therefore.